(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights one of the main directions of the Jadid movement that emerged in the late 19th and early 20th centuries - Jadid schooling and its role in socio-spiritual life. In particular, the educational views of Said Rizo Alizoda, one of the prominent representatives of this movement, his contribution to reforms, and his practical activities in establishing new-method schools are analyzed. Alizoda’s efforts to modernize schools and madrasas based on contemporary requirements, his role in the national-educational awakening, and the significance of his legacy in today’s education system are examined on a scientific basis.